PENGEMBANGAN PROSES BELAJAR MENGAJAR MELALUI SIMULASI DAN MODUL AJAR INTERAKTIF DALAM CD ROM PADA MATA KULIAH ASPEK HUKUM PEMBANGUNAN - M. Agung Wibowo (Diponegoro University, 2008)
Learning Process Needs Improvement On The Way To Deliver The Subjects To The Students. This IsBecause The Aspect Surounding The Subjects Or The Material Are Keep Changing Inherent With TheDynamic Social And Economic Change Of The Society.There Are Many Types Of How To Deliver The Subjects To The Students. It Can Start From SeminarThrough Discussion. Among All Of Types, Simulation Is One Of The Types Where The Students CouldParticipate Actively To Act As Person On The Real Industry.The Simulation Method Is Chosen To Deliver A Subjet Of Construction Law Including A ProcurementProcess To The Students. On The Procurement Method Especially For Government Goods And Services,There Are Many Aspects That The Student Should Know. However, Many Terms Are Not Easily FiguredOut On Some Occasion During Tender And Bidding Phase. By Doing Simulation, The Student Could ActAs Person Who Incharge On Tender And Bidding Process Whether As The Committee Or As TheContractor, Consultant And Supplier.A Modul Was Developed As Well As A Student’s Guidance. This Modul Was Based On Some EmpiricalInvestigation And Previous Literature Review On The Construction Law Especially On The ProcurementMethod.